Correlation Between Avalanches and Emitted Energies During Fracture With a Variable Stress Release Range - Bodaballa, Narendra K.; Biswas, Soumyajyoti; Roy, Subhadeep (Frontiers in Physics, 2022)
We observe the failure process of a fiber bundle model with a variable stress release range, $γ$, higher the value of $γ$ lower the stress release range. By tuning $γ$ from low to high, it is possible to go from the mean-field (MF) limit of the model to the local load sharing (LLS) limit where local stress concentration plays a crucial role. In the MF limit, individual avalanches (number of fibers breaking in going from one stable state to the next, $s$) and the corresponding energies $E$ emitted during those avalanches, have one-to-one linear correlation. This results in the same size distributions for both avalanches ($P(s)$) and energy bursts ($Q(E)$): a scale-free distribution with a universal exponent value -5/2. With increasing $γ$, the model enters the LLS limit beyond some $γ_c$. In this limit, due to the presence of local stress concentrations around a damaged region, such correlation $C(γ)$ between $s$ and $E$ decreases, i.e., a smaller avalanche can emit a large amount of energy or a large avalanche may emit a small amount of energy. The nature of the decrease in the correlation between $s$ and $E$ depends highly on the dimension of the bundle. In this work, we study the decrease in the correlation between avalanche size and the corresponding energy bursts with an increase in the load redistribution localization in the fiber bundle model in one and two dimensions. Additionally, we note that the energy size distribution remains scale-free for all values of $γ$, whereas the avalanche size distribution becomes exponential for $γ>γ_c$.